The skinny on teaching : what you don't learn in graduate school - Anderson, J. M. (Emerald Publishing Limited : Information Age Pub., 2011)
This book is a straightforward and entertaining primer on college teaching. It discusses the nitty-gritty aspects of teaching while providing readers with a synoptic but concise explanation of the principles of the art. It also offers a viable alternative to the books on teaching currently available or in print. That alternative is the classic texts on education and pedagogy. These books are essential, the author argues, because they show teachers how to apply the principles of teaching while fostering the aims of liberal education at the same time. These books also help them pose the fundamental questions about education that all teachers should be asking.Aimed primarily at graduate students and new college professors, this book is a useful and practical guide for those who are passionate about teaching but feel unprepared to teach, unsure of what to expect in the classroom, and stifled in the current academic climate. It will likewise appeal to high school teachers and veteran college professors who are disenchanted and seek some way to break free from their malaise. It is intentionally short, little, "skinny," so that it can be read through quickly and so that readers can peruse the chapters and mull over the topics at their leisure. Above all else, this book will introduce a new generation of readers to some of the great masters who can reveal the timeless truths--and yes, even the magic--behind the art.